Enhanced planar perovskite solar cells with efficiency exceeding 16% via reducing the oxygen vacancy defect state in titanium oxide electrode. Issue 21 (12th May 2017) - Du, Yangyang; Cai, Hongkun; Wu, Yunhao; Xing, Zhixue; Li, Zhenglong; Xu, Jian; Huang, Like; Ni, Jian; Li, Juan; Zhang, Jianjun
Abstract : In this work, the influence of oxygen vacancy defect (OVD) in compact titanium oxide (c-TiO2 ) on the performance of planar perovskite solar cells (p-PSCs) is investigated, and the possible mechanisms are also proposed. Abstract : In this work, the influence of oxygen vacancy defect (OVD) in compact titanium oxide (c-TiO2 ) on the performance of planar perovskite solar cells (p-PSCs) is investigated, and the possible mechanisms are also proposed. To meet our objective, anatase c-TiO2 thin films with various OVD concentrations are prepared by changing the oxygen flux during the DC magnetron sputtering process and are characterized by the intensity of defect signals in the X-ray photoelectron spectra. We conclude that abundant OVDs can trigger an obviously increased majority carrier accumulation zone at the metal oxide/perovskite interface and enhanced capacitance, thereby greatly deteriorating photogenerated carrier collection efficiency. A detailed analysis of the study results also reveals that the presence of OVD in the bulk and surface of c-TiO2 can slow down electronic carrier transport and lower its electron quasi-Fermi level under illumination, leading to the detrimental charge recombination in p-PSCs. Furthermore, we report a remarkably enhanced p-PSC efficiency via preparing c-TiO2 using high oxygen flux and subsequent ultraviolet ozone treatment. As a consequence, repeatable power conversion efficiency (PCE) is propelled to as high as 16.62%, coupled with negligible hysteresis and increased stability. These results provide a significant implication for further perfecting efficient and stable p-PSCs for their record efficiency.